Cholinergic basal forebrain neurons project to cortical microvessels in the rat: electron microscopic study with anterogradely transported Phaseolus vulgaris leucoagglutinin and choline acetyltransferase immunocytochemistry - Vaucher, E (J Neurosci, 1995)
Physiological evidence indicates that central cholinergic pathways are involved in the regulation of cerebral cortical blood flow. We investigated the possible contribution of basal forebrain cholinergic neurons from the substantia innominata (SI) to the innervation of cortical microvessels. Basalo-cortical perivascular nerve terminals were detected by light and electron microscopic immunocytochemistry of anterogradely transported Phaseolus vulgaris leucoagglutinin (PHA-L) following its injection in the SI, and were compared to cortical perivascular cholinergic (immunoreactive for choline acetyltransferase (ChAT)) terminals. The basal forebrain origin of cholinergic terminals was evaluated after unilateral ibotenic acid lesion of the SI. PHA-L varicose fibers reached and surrounded microvessels in all cortical subdivisions examined. When studied at the ultrastructural level in the fronto-parietal and perirhinal cortices, perivascular PHA-L nerve terminals were located significantly closer to microvessels in the fronto-parietal than in the perirhinal cortex (respective average distance of 0.98 +/- 0.09 and 1.34 +/- 0.07 micron; p < 0.01). PHA-L and ChAT terminals in the fronto-parietal cortex compared very well in their perivascular distribution but not in the perirhinal cortex. In both cortices, perivascular PHA-L terminals were similar in size to, but engaged more frequently in synaptic contacts than their ChAT counterparts. Following SI lesion, the density of cortical ChAT terminals including those reaching microvessels decreased significantly (56 and 63%, respectively, p < 0.005) in the fronto-parietal cortex, while the cortical and perivascular denervations were much less pronounced (26%, not significant and 35%, p < 0.05, respectively) in the perirhinal cortex. These results indicate that basal forebrain neurons project preferentially to fronto-parietal cortical microvessels and further show that a significant proportion of these projections are cholinergic. In addition, the difference in distribution and/or synaptic incidence between perivascular PHA-L and ChAT terminals suggested that noncholinergic SI neurons also contribute to these neurovascular associations, and more so in the perirhinal cortex, as further indicated by the lesion studies. Such finding corroborates recent physiological evidence for a functional innervation of the cortical microvascular bed by SI neurons, a role that might be relevant to the overall pathology of Alzheimer's dementia.